Independence Day celebration in growing the spirit of nationalism in Sukahurip Village - Nur Ani Gunawan; Indri Dwinda Putri (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Commemoration of the Independence Day of the Republic of Indonesia is one of the programs held by UPI KKNT students in Sukahurip Village. This service documents and analyzes competition activities commemorating the 78th Indonesian Independence Day in Sukahurip Village. Activities involve competitions such as carnivals, dongdang, and gate decorating, aiming to foster a feeling of love for the country, remembering the nation's struggle's history, and appreciating Indonesian culture's noble values and diversity. The competition activity created a moment of togetherness and patriotism in Sukahurip Village. Through the creativity and innovation displayed in each competition, people are inspired to get involved in the development of their region. Social solidarity is strengthened primarily through active participation in the preparation and implementation of dongdang competitions. Suggestions for further programs could include integration of vertical and horizontal approaches, active community participation in planning, long-term impact evaluation, analysis of community welfare, comparative studies with similar villages, development of local development models, and further studies on the role of KKN students. Hopefully, this service program can contribute to understanding the impact of competition activities in Sukahurip Village.   Abstrak Peringatan hari Kemerdekaan Republik Indonesia menjadi salah satu program yang diadakan oleh mahasiswa KKNT UPI di Desa Sukahurip. Pengabdian ini mendokumentasikan dan menganalisis kegiatan perlombaan yang diselenggarakan selama peringatan HUT RI ke-78 di Desa Sukahurip. Kegiatan melibatkan berbagai lomba seperti karnaval, dongdang, dan menghias gapura, dengan tujuan memupuk rasa cinta tanah air, mengenang sejarah perjuangan bangsa, dan menghargai nilai-nilai luhur dan keberagaman budaya Indonesia. Kegiatan perlombaan berhasil menciptakan momen kebersamaan dan semangat patriotisme di Desa Sukahurip. Melalui kreativitas dan inovasi yang ditampilkan dalam setiap lomba, masyarakat terinspirasi untuk terlibat dalam pembangunan daerah mereka. Solidaritas sosial diperkuat, terutama melalui partisipasi aktif dalam persiapan dan pelaksanaan lomba dongdang. Saran untuk program selanjutnya dapat mencakup integrasi pendekatan vertikal dan horizontal, partisipasi aktif masyarakat dalam perencanaan, evaluasi dampak jangka panjang, analisis kesejahteraan masyarakat, studi komparatif dengan desa serupa, pengembangan model pembangunan lokal, dan studi lanjutan tentang peran mahasiswa KKN. Program pengabdian ini diharapkan dapat memberikan kontribusi yang lebih mendalam terhadap pemahaman dampak kegiatan perlombaan di Desa Sukahurip.  Kata Kunci: Kemerdekaan Republik Indonesia; KKNT UPI; nasionalisme; perayaan kemerdekaan